2022
DOI: 10.3390/ph15030298
|View full text |Cite
|
Sign up to set email alerts
|

A Sex- and Gender-Based Analysis of Adverse Drug Reactions: A Scoping Review of Pharmacovigilance Databases

Abstract: Drug-related adverse events or adverse drug reactions (ADRs) are currently partially or substantially under-reported. ADR reporting systems need to expand their focus to include sex- and gender-related factors in order to understand, prevent, or reduce the occurrence of ADRs in all people, particularly women. This scoping review describes adverse drug reactions reported to international pharmacovigilance databases. It identifies the drug classes most commonly associated with ADRs and synthesizes the evidence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 61 publications
5
30
0
Order By: Relevance
“…Similar findings were shown in a study by Oliver Pascale et al and could be due to the fact that this population is attending hospital more frequently and is a major population receiving drug therapy [21]. A positive association between incidence of ADR and increasing age was as well found which was consistent with the findings of Barbate et al [9].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Similar findings were shown in a study by Oliver Pascale et al and could be due to the fact that this population is attending hospital more frequently and is a major population receiving drug therapy [21]. A positive association between incidence of ADR and increasing age was as well found which was consistent with the findings of Barbate et al [9].…”
Section: Discussionsupporting
confidence: 91%
“…Surprisingly, there are instances where, ADR-related costs, such as hospitalization, surgery and lost productivity, far exceed the cost of the medications [3,7]. The recent epidemiological studies have reported that ADR are the fourth to sixth leading causes of death [1,8,9]. The WHO defined "Pharmacovigilance" as "The science and activities related to the detection, assessment, understanding and prevention of adverse drug effects or any other possible drug-related problems [3,10]."…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, the female gender is the one that most notified to any drug, due to the greater susceptibility to develop ADRs, compared to the male gender, probably due to the physiological differences between both sexes. Additionally, it may be related to women’s greater attention to their health and signals developed by their body [ 29 , 32 , 33 ]. International studies also confirm the aforementioned data regarding the age groups and gender with the highest notification rates of vaccine-associated ADRs [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similar to what was found in this research, an increase of ADRs in females have already been reported. The literature divides this event into two main aspects, those related to gender (more informed on health issues, concern about your health, a propensity to report symptoms, increased interest in reporting) [25,26], and those related to sex (metabolic, pharmacokinetic, pharmacodynamic, and hormonal factors) [27,28]. It is possible that factors related to sex could be influencing the increase in ADRs in the active surveillance database.…”
Section: Discussionmentioning
confidence: 99%